2016
DOI: 10.1038/srep25882
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into blood microbiota and its potential association with Bacterial Chondronecrosis with Osteomyelitis (BCO) in Broilers

Abstract: Bacterial chondronecrosis with osteomyelitis (BCO) is a common cause of lameness in commercial broiler chickens worldwide. BCO represents substantial production loss and welfare issues of chickens. The bacterial species or communities underlying BCO pathogenesis still remain to be fully characterized. To gain insights on blood microbiota in broilers and its potential association with BCO, blood samples collected from healthy (n = 240) and lame (n = 12) chickens were analyzed by deep sequencing of 16S RNA genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 44 publications
6
61
0
Order By: Relevance
“…Most of the blood bacterial DNA was found located in the BC (93.74%), while RBCs contain more bacterial DNA (6.23%) than the plasma (0.03%) [14]. A significant number of bacterial species were also detected in the blood of healthy chickens [16] …”
Section: Tedeschi Et Al Reported On Incorporation Of Nucleosides In mentioning
confidence: 83%
See 1 more Smart Citation
“…Most of the blood bacterial DNA was found located in the BC (93.74%), while RBCs contain more bacterial DNA (6.23%) than the plasma (0.03%) [14]. A significant number of bacterial species were also detected in the blood of healthy chickens [16] …”
Section: Tedeschi Et Al Reported On Incorporation Of Nucleosides In mentioning
confidence: 83%
“…We note, that some phyla are enriched by the applied resuscitation strategy according to the OTUs combined abundancy (Table 1). Other studies also identified Proteobacteria as predominant in the blood of healthy individuals [14], healthy broilers [16] and cats [17].…”
Section: Resultsmentioning
confidence: 99%
“…The possible contamination of the DNA might be the reason for getting Rhodococcus, Pseudomonas or microbacterium, Bacillus and Sphin- gomonas in bird blood where we were expecting rickettsial reads (Weiss et al, 2014). We were not ruling out blood as sterile as there were reports of microbiota detected in bird blood (Mandal et al, 2016). Although, our results rule out possibility of migratory birds being reservoir host, birds can be rickettsiamic with Rickettsia helvetica (Hornok et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…General pipelines for data analysis was previously described in details (Mandal et al, 2016). Forward and reverse ends sequences were joined together by using join_paired_ends.py command followed by formatting barcodes using customized Perl script, before extracting barcodes using extract_barcodes.py option.…”
Section: Methodsmentioning
confidence: 99%